Long-range magnetic ordering in Ba2COS3: A neutron diffraction study - Headspith, D; Battle, P; Francesconi, MG (2007)
Neutron powder diffraction has been used to determine the magnetic structure of the quasi-one-dimensional compound Ba2CoS3, which contains linear [001] chains of vertex-sharing CoS4 tetrahedra, spaced apart by Ba2+ cations. At 1.5 K the Co2+ cations in the chains are antiferromagnetically ordered with an ordered magnetic moment of 1.97(4) μB per cation aligned along [100]. Each Co2+ cation is ferromagnetically aligned with four cation in neighbouring chains and antiferromagnetically aligned with two others. © 2007 Elsevier Inc. All rights reserved.